3D bioprinting of cartilaginous templates for large bone defect healing. (15th January 2023) - Pitacco, Pierluca; Sadowska, Joanna M.; O'Brien, Fergal J.; Kelly, Daniel J.
Abstract: Damaged or diseased bone can be treated using autografts or a range of different bone grafting biomaterials, however limitations with such approaches has motivated increased interest in developmentally inspired bone tissue engineering (BTE) strategies that seek to recapitulate the process of endochondral ossification (EO) as a means of regenerating critically sized defects. The clinical translation of such strategies will require the engineering of scaled-up, geometrically defined hypertrophic cartilage grafts that can be rapidly vascularised and remodelled into bone in mechanically challenging defect environments. The goal of this study was to 3D bioprint mechanically reinforced cartilaginous templates and to assess their capacity to regenerate critically sized femoral bone defects. Human mesenchymal stem/stromal cells (hMSCs) were incorporated into fibrin based bioinks and bioprinted into polycaprolactone (PCL) frameworks to produce mechanically reinforced constructs. Chondrogenic priming of such hMSC laden constructs was required to support robust vascularisation and graft mineralisation in vivo following their subcutaneous implantation into nude mice. With a view towards maximising their potential to support endochondral bone regeneration, we next explored different in vitro culture regimes to produce chondrogenic and early hypertrophic engineered grafts. Following their implantation into femoral bone defects within transiently immunosuppressed rats, such bioprinted constructs were rapidly remodelled into bone in vivo, with early hypertrophic constructs supporting higher levels of vascularisation and bone formation compared to the chondrogenic constructs. Such early hypertrophic bioprinted constructs also supported higher levels of vascularisation and spatially distinct patterns of new formation compared to BMP-2 loaded collagen scaffolds (here used as a positive control). In conclusion, this study demonstrates that fibrin based bioinks support chondrogenesis of hMSCs in vitro, which enables the bioprinting of mechanically reinforced hypertrophic cartilaginous templates capable of supporting large bone defect regeneration. These results support the use of 3D bioprinting as a strategy to scale-up the engineering of developmentally inspired templates for BTE. Statement of significance: Despite the promise of developmentally inspired tissue engineering strategies for bone regeneration, there are still challenges that need to be addressed to enable clinical translation. This work reports the development and assessment ( in vitro and in vivo ) of a 3D bioprinting strategy to engineer mechanically-reinforced cartilaginous templates for large bone defect regeneration using human MSCs. Using distinct in vitro priming protocols, it was possible to generate cartilage grafts with altered phenotypes. More hypertrophic grafts, engineered in vitro using TGF-β3 and BMP-2, supported higher levels of blood vessel infiltration and accelerated bone regeneration in vivo . This study also identifies some of the advantages and disadvantages of such endochondral bone TE strategies over the direct delivery of BMP-2 from collagen-based scaffolds. Graphical abstract: Image, graphical abstract